2021
DOI: 10.3389/fpls.2021.714066
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Function of OsFBX267 and OsGA20ox2 in Rice Promotes Early Maturing and Semi-Dwarfism in γ-Irradiated IWP and Genome-Edited Pusa Basmati-1

Abstract: Targeted mutagenesis is now becoming the most favored methodology to improve traits in popular rice cultivars selectively. Understanding the genetic basis of already available mutants could be the first step in designing such experiment. Improved White Ponni (IWP), a popularly grown South Indian rice variety, was subjected to γ irradiation to develop WP-22-2, an M6 line superior in semi-dwarfism, early flowering, and high yield, and it has grain qualities similar to those of IWP. The exogenous application of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…After pyramiding the favorable alleles located on these five loci into a single genotype, the PH could be reduced by −30.57 cm. A moderate plant height is an important basis for rice breeding, and this is supported by Andrew-Peter-Leon, et al [ 40 ] and Bhuvaneswari, et al [ 41 ], who have reported that OsGA20ox2 and OsFBX26 , have important roles in regulating semi-dwarfism and early flowering in rice. Likewise, this finding is supported by Liu, et al [ 29 ], who reported that several semi-dwarf rice varieties have been bred by genetic introduction of the mutant alleles of SD1, which encodes OsGA20ox2 for catalyzing GA biosynthesis.…”
Section: Discussionmentioning
confidence: 95%
“…After pyramiding the favorable alleles located on these five loci into a single genotype, the PH could be reduced by −30.57 cm. A moderate plant height is an important basis for rice breeding, and this is supported by Andrew-Peter-Leon, et al [ 40 ] and Bhuvaneswari, et al [ 41 ], who have reported that OsGA20ox2 and OsFBX26 , have important roles in regulating semi-dwarfism and early flowering in rice. Likewise, this finding is supported by Liu, et al [ 29 ], who reported that several semi-dwarf rice varieties have been bred by genetic introduction of the mutant alleles of SD1, which encodes OsGA20ox2 for catalyzing GA biosynthesis.…”
Section: Discussionmentioning
confidence: 95%
“…GA20OX2 ) or overexpression of catabolic genes (e.g. GA2OX6 ) leads to dwarfism by reducing endogenous GA levels (Andrew‐Peter‐Leon et al ., 2021 ; Yan et al ., 2017 ). The expression of these GA metabolic genes is also regulated by exogenous GA, whose biosynthesis genes are repressed after GA treatment (Wang et al ., 2015 ).…”
Section: Discussionmentioning
confidence: 99%